Attribution of historical near-surface permafrost degradation to anthropogenic greenhouse gas warming. (11th August 2020) - Guo, Donglin; Sun, Jianqi; Li, Huixin; Zhang, Tingjun; Romanovsky, Vladimir E
Abstract: Given the current confirmed permafrost degradation and its considerable impacts on ecosystems, water resources, infrastructure and climate, there is great interest in understanding the causes of permafrost degradation. Using the surface frost index (SFI) model and multimodel data from the fifth phase of the Coupled Model Intercomparison Project (CMIP5), this study, for the first time, investigates external anthropogenic and natural forcing impacts on historical (1921–2005) near-surface permafrost change in the Northern Hemisphere. The results show that anthropogenic greenhouse gas (GHG) forcing produces a significant decrease in the area of near-surface permafrost distribution at a rate of 0.46 × 10 6 km 2 decade −1, similar to observations and the historical simulation (ALL). Anthropogenic aerosol (AA) forcing yields an increase in near-surface permafrost distribution area at a rate of 0.25 × 10 6 km 2 decade −1 . Under natural (NAT) forcing, there is a weak trend and distinct decadal variability in near-surface permafrost area. The effects of ALL and GHG forcings are detectable in the observed change in historical near-surface permafrost area, but the effects of NAT and AA forcings are not detected using the optimal fingerprint methods. This indicates that the observed near-surface permafrost degradation can be largely attributed to GHG-induced warming, which has decreased the near-surface permafrost area in the Northern Hemisphere by approximately 0. 21 × 10 6 km 2 decade −1 on average over the study period, according to the attribution analysis.